Aplicação dos registros de representação semiótica no ensino-aprendizagem da matemática: um estudo com alunos do sexto ano do ednsino fundamental - Neres, Raimundo Luna [UNESP] (2010)
Semiology Presentation Register, applying theory to Mathematics teaching-learning process. This paper aimed to check whether there was a better student performance after Semiology Presentation Register being applied to Mathematics, that is, with regards to solving problems, natural numbers resolutions for the 6th grade fundamental school children at COLUN – Colégio Universitário (UFMA College School). The first task consisted of a list of exercises based on Semiology Presentation Register with ten problems aiming to measure students performance level. From the analysis of the data collected, a study plan was elaborated based on the mathematics book contents adopted by the school. During the research, several meetings were held with the students teacher to detect if there was any improvement on students performance, and thus adjust the way contents would be developed in the classroom on Presentation Register Theory applied to. In observing the daily classroom, several types of evaluations were made, such as single and groups exercises, in order to secure improvement and school performance. The applying of study, approach and semiology conversions, related to evaluation and classroom activities, were made at random in order to guarantee analysis’ data impartiality. As the research result it was found out that nearly 60% of students had suitable improvement (good: 61% – 80%) and 37% had fair improvement (fair: 41% – 60%). It was also found out that about 3% of students did not show any problem solution whatsoever. Those results show that it was possible to improve school performance on Mathematics for the researched students.